2023
DOI: 10.1085/jgp.202213150
|View full text |Cite
|
Sign up to set email alerts
|

Remodeled connexin 43 hemichannels alter cardiac excitability and promote arrhythmias

Abstract: Connexin-43 (Cx43) is the most abundant protein forming gap junction channels (GJCs) in cardiac ventricles. In multiple cardiac pathologies, including hypertrophy and heart failure, Cx43 is found remodeled at the lateral side of the intercalated discs of ventricular cardiomyocytes. Remodeling of Cx43 has been long linked to spontaneous ventricular arrhythmia, yet the mechanisms by which arrhythmias develop are still debated. Using a model of dystrophic cardiomyopathy, we previously showed that remodeled Cx43 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…TRPV4-activation induced a strongly ethidium uptake in ECs during the time (Figure 2D). Either inhibition of NO production with 100 µM L-NAME or the blockade of Cx43 hemichannels with 50 µM β-glycyrrhetinic acid (β-GA) or 50 µM Gap19-TAT, a specific Cx43 hemichannel blocker 15,16,24,25 , significantly reduced dye uptake increases. (Figure 2D).…”
Section: Trpv4 Associates Closely With Cx43 and Its Activation Promot...mentioning
confidence: 99%
See 2 more Smart Citations
“…TRPV4-activation induced a strongly ethidium uptake in ECs during the time (Figure 2D). Either inhibition of NO production with 100 µM L-NAME or the blockade of Cx43 hemichannels with 50 µM β-glycyrrhetinic acid (β-GA) or 50 µM Gap19-TAT, a specific Cx43 hemichannel blocker 15,16,24,25 , significantly reduced dye uptake increases. (Figure 2D).…”
Section: Trpv4 Associates Closely With Cx43 and Its Activation Promot...mentioning
confidence: 99%
“…In myoendothelial junctions, Snitrosylated Cx43 gap junction channels are crucial for regulating vascular diameter by facilitating the transmission of vital vasoactive molecules, such as Ca 2+ , IP 3 , NO, between endothelial and smooth muscle cells 12,13 . S-nitrosylation of Cx43 has been also shown to activate undocked hemichannels at the plasma membrane, influencing the membrane excitability of cardiomyocytes [14][15][16] . Specifically, they play pivotal roles in cardiac action potentials and the influx of Ca 2+ into cardiomyocytes under both normal conditions and during cardiac dysfunction 14,16,17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that Cx43-mediated arrhythmias are a complex phenomenon that extends beyond alterations in ion conduction via GJCs. It has been also demonstrated that Cx43 can form hemichannels that can open to the plasma membrane, allowing ion flux into the extracellular space and affecting cardiomyocyte excitability [76]. Consequently, Cx43 hemichannels have been proposed as potential targets for the arrhythmia treatment [74,77].…”
Section: Connexins General Characteristicsmentioning
confidence: 99%
“…Different GJCs also take an active role in cell growth and differentiation, tissue development and homeostasis 11 , and disruptions of connexin function can lead to severe pathological conditions. For example, dysfunctions in different connexin channels have been linked to deafness (Cx26) 12 , cataracts (Cx46 and Cx50) 13 , peripheral neuropathy (X-linked Charcot-Marie-Tooth disease, Cx32) 14 , cardiac arrhythmias (Cx40 and Cx43) 15,16 and various forms of cancer 17 .…”
Section: Introductionmentioning
confidence: 99%